Minat Berzakat Generasi Milenial Indonesia - Muhammad Sukrianto (Biro Perencanaan Kementerian Agama, 2023)
Abstract The purpose of this study is to identify the factors influencing the intention of Indonesian millennials to pay zakat.The study used the Theory of Reasoned Action (TRA), the extended Theory of Planned Behavior (TPB), and the Technology Acceptance Model (TAM) – to investigate the factors influencing the behavioral intention of Indonesian millennials to pay zakat. The theories introduce four variables (i.e., attitude, trust in zakat institution, religiosity, and electronic payment) in predicting their intention to pay zakat. The data were obtained from 394 millennial Moslems who live in several cities in Indonesia. The method applied was a purposive sampling of Indonesian millennial Moslems who are already working and must pay zakat. The data were analyzed using structural equation modeling (SEM) via Amos software. The results of the study show that attitude, trust in zakat institution, religiosity, and electronic payment are statistically significant in influencing the intention of millennial Moslems in Indonesia to pay zakat. The study significantly contributes to the Zakat institution in Indonesia to plan, strategize, and implement an effective intervention by stressing the importance of intention in forming the behavior of millennials in paying zakat. However, the limitation is that this study only focuses on Indonesian millennials, therefore, a cross-generational study may be performed in the future to understand the similarities and differences across generations. Keywords: Zakat, Indonesia, Moslem, Millennials, Intention, Attitude, Trust, Religiosity, Electronic payment.